The linkage between capital structure and financial performance: a case of selected technological firms listed in Johannesburg stock exchange - Khenisa, Boipelo (My University, 2022)
The main objective of this study is to analyse the effect of capital structure on the financial performance of technological firms listed on the Johannesburg Stock Exchange in South Africa. Cross-sectional time-series data was collected from a sample of 14 technological firms over 9 years, yielding a total of 126 observations. The Levin, Lin & Chu test was used to conduct unit root tests on financial performance, capital structure, firm size, firm growth, and macroeconomic control variables. Results indicate that some series were stationary at a level and some at first difference. While return on assets was used as a dependent variable or proxy of financial performance, and debt/equity ratio as a proxy of capital structure, the random effects model was selected in preference to the Fixed Effects model using the Hausman test. Estimates of the random effects model show that the debt/equity ratio had negative and statistically insignificant effects on firms’ financial performance positions. Conversely, the size of the organization and its growth had statistically positive and significant effects on financial performance, with firm size having a more pronounced effect relative to firm growth. The adjusted Rsquared shows that nearly 97 percent of the variation in technological firms’ financial performances is explained by capital structure, firm size, firm growth, and liquidity. Robust checks from stepwise regression results are consistent with the estimates of the random effects model. This study recommends that the management of technological firms should maintain levels of debt that are optimal to avoid the negative effects of high debt burdens on a firm’s financial performance positions.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management in Finance and Investments
Keywords: Capital structure; Financial performance; Return on Asset; Debt-to-equity ratio, Liquidity; Firm size; SDG-8: Decent work and economic growth